Optimalisasi Pendidikan Literasi Pada Anak Usia Dini Melalui Metode Berkisah Islami - Maulida, Maulida (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
Islamic storytelling is an alternative method for optimizing literacy education in early childhood.Children are given Islamic stories by their parents and teachers. If the story is applied by parents,the most effective way is to talk about child bedtime. Whereas if done at school it can beapplied through a learning process using Islamic storytelling. This method has not been widelyused by parents and teachers. Children given Islamic stories by parents and teachers from anearly age, of course, will improve aspects of child development. Not only that, children who arealways given Islamic stories or stories will certainly add insight to children and can optimizeliteracy education. One of them will be happy and love to read or write. Children's interest inliteracy education can develop optimally and optimally. The use of the method of Islamicstorytelling from an early age is expected to be one of the efforts that can be done to overcomevarious behavioral problems in children, while at the same time instilling interest in readingchildren from an early age. Especially on cognitive aspects, moral and religious values, andaspects of children's language development. This paper is intended to provide a morecomprehensive understanding of literacy education with Islamic storytelling methods, andexplore various scientific evidence that can provide logical knowledge for parents, as well asteachers